2023
DOI: 10.3389/fimmu.2023.1126351
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and COVID19 vaccination across eight immune-mediated inflammatory disorders: A prospective, real-life Belgian cohort study – the BELCOMID study

Abstract: BackgroundThe risks and impact of COVID19 disease and vaccination in patients with Immune Mediated Inflammatory Diseases (IMID) remain incompletely understood. IMID patients and particularly patients receiving immunosuppressive treatment were excluded from the original, registrational phase-3 COVID19 vaccination efficacy and safety trials. Real-world observational data can help to fill this gap in knowledge. The BELCOMID study aims to explore the interaction between IMIDs, immune-modulating treatment modalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Although not completely, most patients exhibited the primary components of circulating (or tissue) adaptive immunity. Other authors found similar results; our study confirms them in a longer time frame [ 28 ]. The improving clinical outcomes of COVID-19 in IMIDs observed during the pandemic may also be related to the fact that our data come from the frequent cases of those who received a three-vaccine regimen and then had SARS-CoV-2 infection [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although not completely, most patients exhibited the primary components of circulating (or tissue) adaptive immunity. Other authors found similar results; our study confirms them in a longer time frame [ 28 ]. The improving clinical outcomes of COVID-19 in IMIDs observed during the pandemic may also be related to the fact that our data come from the frequent cases of those who received a three-vaccine regimen and then had SARS-CoV-2 infection [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recent data suggest that pre-existing auto-immune disease is associated with increased severity of COVID-19, but IBD was not the most frequent auto-immune disease in the dataset and the same study showed a protective effect of anti-TNF therapy, which is the most frequently used in patients with IBD ( 38 ). Conversely, the BELCOMID study described a benign course of COVID-19 infection in a cohort of more than 2000 patients with immune mediated inflammatory diseases (IMID) of whom more than 60% had IBD ( 39 ). The MICI-SARS-CoV-2 study provides physicians with data on this specific population of patients with IBD theoretically immunocompromised by their biological therapy before the start of the vaccination campaign.…”
Section: Discussionmentioning
confidence: 99%